Chemical Examination of the seeds of Tecoma undulata - Om Prakash, E.; Rao, J.T. (Asian Journal of Chemistry, 2010)
The carbohydrates and proteins have been analysed from the seeds ofTecoma undulata. The seeds having high nutritional properties are used incattle feed industries.